35.7k views
5 votes
可二人十
Help solve this problem

可二人十 Help solve this problem-example-1
User Panos Boc
by
5.0k points

1 Answer

3 votes
Hi! This is my first time helping someone so I hope this helps!

X=1
Y=5

First in the first equation, subtract x on both sides.

Y= 6-x

Then substitute that into the second equation.

-3x + 6-x = 2

-4x + 6= 2

-4x = -4

x= 1

Substitute it to the first equation

Y= 6-1

Y= 5

X= 1

Hope this helps. I hope you have a great day!

User Stephane Godbillon
by
5.2k points